Tourist Movement Patterns as an Evaluation Indicator for Mandalika-Mataram Tourism Planning - Dimas Arya Andhika; Jamiatun; Muhammad Ardiansyah; Alfian Adhiswara; Putri Mardiah; Gita Safitri (Journal of Governance and Spatial Planning, 2026)
Visitor movement patterns provide an important basis for spatial and transportation planning considerations because they reflect how planned infrastructure operates in real life. Using tourist movement patterns in the Mandalika-Mataram corridor, West Nusa Tenggara Province, Indonesia, as an indicator for channeling tourism planning, this study aims to conduct this analysis. The study focuses on three main movement hubs: Mataram City as a service and transit hub, Lombok International Airport as the main entry point, and Mandalika, a tourist area, as the primary destination. A node-link model based on secondary geospatial data, such as road networks, administrative boundaries, and the distribution of tourist destinations, was used in a spatial analytic technique. The concentration of tourist movements between nodes, movement direction, and network structure were all examined using Geographic Information System (GIS) technologies. The findings indicate that the Mandalika tourist region, the airport, and Mataram City are connected by a linear north-south structure of tourist movement patterns. While ancillary road networks have a smaller importance, tourist movements are mostly centered along the major corridor connecting these nodes. This trend suggests that real tourist mobility and the planned spatial arrangement are closely related. The study comes to the conclusion that visitor mobility patterns can be a useful metric for assessing how well tourism spatial design is working. The concentration along a single corridor emphasizes the necessity of strengthening supporting networks to promote spatial connectedness, even though the current planning effectively directs movement toward important tourist attractions.